Life on the seesaw: Tensions in an Action Reflection LearningTM program - ARL Inquiry (Adult Education Research Conference, 1995)
As organizations increasingly recognize a need for continuous learning, adult educators are gaining interest in techniques that will enable people to learn from their work. The literature suggests that people learn better when dealing with issues important to them. In the real world, however, important, strategic issues have deadlines and perceived constraints. This paper examines some of the tensions created between learning, and the action that needs to be taken to resolve these strategic issues in an Action Reflection LearningTM program.